El final de las escrituras paleohispánicas (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this paper is to determine the chronology of the most modern inscriptions written in Paleohispanic semi-sillabary. Although not all the typologies allow us to establish with absolute certainty the dating of the items, the coin legends and the graffiti scratched on imported ware are the more reliable. For that reason, this paper deals with graffiti scratched on samian ware (terra sigillata) and other ceramic productions datable in the imperial period, since they are the most modern texts written in Paleohispanic semi-sillabary.
Keywords: Graffiti; Paleohispanic Semi-sillabary; Latinization